Production of minitubers from vine cuttings of white yam (Dioscorea rotundata) - Oyetunji, O.J.; Kabeya, M.; Shiwachi, H. (2007)
The multiplication ratio for seed yam production is very low compared to other tuberous crops. Seven clones of Dioscorea rotundata Poir (white yam) were evaluated for production of mini tubers from their vine cuttings. Three to four nodes leafy vine cuttings were prepared from the middle portion of the lateral branches collected from mother plants 127, 134 and 141 days after planting (DAP). The lower portion of these nodes were wounded with a clean razor blade and then dusted with 1.0% Indole-3 butyric acid (IBA) powder in order to promote rooting. The mini tubers were harvested 115 DAP. The developed mini tubers varied in sizes among the tested cultivars from 1.9 to 4.2g. The weights were found to be genotype dependent. The survival rate of the planted vine cuttings ranged from 31.1 to 77.1% while the average total number of roots per vine ranged from 5.1 to 5.8. The average number of tubers per vine was 1.8 ±0.8. If these number and weights of mini tubers can be obtained from propagation of vine cuttings, there will be tremendous increase in propagating material thereby making yam cultivation less expensive and also allowing the ware yam only for consumption and other uses.